Early family system types predict children's emotional attention biases at school age. (March 2017) - Lindblom, Jallu; Peltola, Mikko J; Vänskä, Mervi; Hietanen, Jari K; Laakso, Anu; Tiitinen, Aila; Tulppala, Maija; Punamäki, Raija-Leena
The family environment shapes children's social information processing and emotion regulation. Yet, the long-term effects of early family systems have rarely been studied. This study investigated how family system types predict children's attentional biases toward facial expressions at the age of 10 years. The participants were 79 children from Cohesive, Disengaged, Enmeshed, and Authoritarian family types based on marital and parental relationship trajectories from pregnancy to the age of 12 months. A dot-probe task was used to assess children's emotional attention biases toward threatening (angry) and affiliative (happy) faces at the early (500 ms) and late (1250 ms) stages of processing. Situational priming was applied to activate children's sense of danger or safety. Results showed that children from Cohesive families had an early-stage attentional bias toward threat, whereas children from Enmeshed families had a late-stage bias toward threat. Children from Disengaged families had an early-stage attentional bias toward threat, but showed in addition a late-stage bias away from emotional faces (i.e., both angry and happy). Children from Authoritarian families, in turn, showed a late-stage attentional bias toward emotional faces. Situational priming did not moderate the effects of family system types on children's attentional biases. The findings confirm the influence of early family systems on the attentional biases, suggesting differences in the emotion regulation strategies children have developed to adapt to their family environments.